2003
DOI: 10.1128/iai.71.1.187-195.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Heterogeneity of Ehrlichia chaffeensis Isolates Determined by Sequence Analysis of the 28-Kilodalton Outer Membrane Protein Genes and Other Regions of the Genome

Abstract: Ehrlichia chaffeensis, a tick-transmitted rickettsial agent, is responsible for human monocytic ehrlichiosis (HME). In this study, we genetically mapped 10 isolates obtained from HME patients. Sequence analysis of the 28-kDa outer membrane protein (OMP) multigene locus spanning 6 of the 22 tandemly arranged genes identified three distinct genetic groups with shared homology among isolates within each group. Isolates in Groups I and III contained six genes each, while Group II isolates had a gene deletion. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 37 publications
2
46
2
Order By: Relevance
“…The three-and six-repeat types of the VLPT gene were the least common variants observed in this study; these variants have been found in infected humans on five occasions and one occasion, respectively. The three-repeat VLPT type has been found in humans only in Georgia, Tennessee, and Nebraska (1,12); however, in the present study this genetic variant was found in WTD from Kansas, thereby extending the geographic distribution of this genetic type. Similarly, the six-repeat VLPT profile has been found only once, in a human from Wakulla Co., Fla. (16).…”
contrasting
confidence: 52%
“…The three-and six-repeat types of the VLPT gene were the least common variants observed in this study; these variants have been found in infected humans on five occasions and one occasion, respectively. The three-repeat VLPT type has been found in humans only in Georgia, Tennessee, and Nebraska (1,12); however, in the present study this genetic variant was found in WTD from Kansas, thereby extending the geographic distribution of this genetic type. Similarly, the six-repeat VLPT profile has been found only once, in a human from Wakulla Co., Fla. (16).…”
contrasting
confidence: 52%
“…It was reported that transcripts of all the p28 omp genes were detected from an infected dog except for the p28-2 gene (22). However, other studies have detected transcripts for fewer p28 genes in cell culture (5,19,22). Differences in the detection of p28 omp gene transcripts by reverse transcription-PCR could be due to experimental variables, such as RNA template quantity and quality, or primer specificity.…”
mentioning
confidence: 76%
“…As the map1-2 gene is present in the Welgevonden and Senegal isolate and could also be amplified from other isolates (data not shown), we assume that the gene is deleted from CTVM Gardel. Cheng et al (9) showed that molecular heterogeneity of E. chaffeensis isolates occurred in the ␣-repetitive region of the cluster, giving rise to three genetic groups containing either 22 (group I and III) or 21 genes (group II). Two locations were identified where insertions and/or deletions occurred (9).…”
Section: Discussionmentioning
confidence: 99%